ANALISIS SIMULASI PERFORMA TURBIN PROPELLER PEMBANGKIT LISTRIK TENAGA MIKROHIDRO PROFIL AIRFOIL NACA 5310 DAN NACA 6412 - Haryadi; Ahmad Zaki Rasyidi; Apri Setiawan; Budi Triyono; Setiawan, Dibyo (JURNAL CRANKSHAFT, 2026)
Renewable energy, particularly hydropower, has become an important alternative in reducing dependence on fossil fuels. One widely used technology is the propeller turbine, which utilizes airfoil-based blade profiles to enhance the conversion of fluid energy into mechanical energy. This study aims to analyze the simulation performance of a propeller turbine with variations of NACA 5310 and NACA 6412 airfoil profiles under low-head conditions. The methodology employed is a numerical simulation based on Computational Fluid Dynamics (CFD). The observed variables include flow rate, pressure distribution, rotational speed, torque, hydraulic power, mechanical power, and turbine efficiency at head variations of 3 m and 5 m. The simulation results indicate that increasing the head from 3 m to 5 m significantly increases the flow rate, torque, and mechanical power; however, the turbine efficiency decreases drastically from approximately 69–71% at a 3 m head to about 30% at a 5 m head. The NACA 6412 profile demonstrates slightly better performance than the NACA 5310 profile, particularly in terms of efficiency and torque stability. Overall, both airfoil profiles are more suitable for low-head operating conditions and therefore have strong potential for application in micro-hydro power plants.